An ε-Minimax Theorem for Bi-Lower-Semicontinuous Set-Valued Mappings. (19th May 2019) - Jin, Caiyun
Abstract: In this article, an approximate minimax theorem for bi-lower-semicontinuous set-valued mapping was proved, relationships between semicontinuous set-valued mappings are discussed and the existence of approximate maxmin was given. The minimax theorem in this article is the first minimax theorem that doesn't require the set-valued mappings to be continuous.